Accessibility of Library Building for People With Disabilities in Jakarta Library - Elfitri Erza; Rahayu Fissilmi Kaffah; Mochammad Wahyu Ghani; Ario Adi Prakoso (Universitas Terbuka, 2024)
The lack of accessibility for people with disabilities in public facilities makes it difficult for people with disabilities to carry out activities and mobility easily, safely, comfortably, and independently, especially in terms of meeting information needs and accessing information needed in libraries. This study aims to find out the implementation of accessibility of library buildings for people with disabilities in the Jakarta-Cikini Library. The research method used is a qualitative approach with a type of case study research. Data collection through observation, interviews, and documentation. The selection of informants in this study used purposive sampling. The results showed that the implementation of accessibility of library buildings for people with disabilities in the Jakarta-Cikini Library can be said to be quite good based on IFLA standard guidelines. There are only a few accessibility that have not been implemented thoroughly such as disability-only parking lots far from the entrance and symbol colors in parking lots that have faded, doors and walls that use glass there are no stickers or warning signs to watch out for glass, the unavailability of an induction loop system at the circulation and information desk, the unavailability of handles to help disabled people standing on the toilet and the absence of the application of guiding blocks Inside the library.